VISUAL REPRESENTATION OF JUVENILE DELINQUENCY: A SEMIOTIC STUDY OF THE FILM 'GALAKSI' BY KUNTZ AGUS - Maharani, Cintya Putri; Rahmawati, Laili Etika (Pena Cendekia Insani, 2025)
Juvenile delinquency is a complex and multidimensional social phenomenon, thus attracting the attention of many parties, including experts, policy makers, and the general public. This study provides insight into how film media influences public perceptions and attitudes towards social issues, particularly juvenile delinquency. By examining the semiotic representation in